Anti-Inflammatory Effect of Ixora coccinea Linn On Stem Cells of Human Exfoliated Deciduous Teeth Cells: Pharmaceutical Science-Dental - Ghazali, Norliana; Mohd Shah, Noor Hafizah; Abd Rahman, Normastura (International Journal of Life Science and Pharma Research, 2023)
Ixora coccinea, commonly known as a jungle of geranium and red Ixora evergreen shrubs found throughout India. The plant is crucial for several medicinal purposes, including inflammation, wound healing, diarrhea, and cancer. This study aimed to determine the anti-inflammatory activity of Ixora coccinea extracts and the expression of inflammatory genes in cell lines treated with Ixora coccinea extracts. First, the roots of Ixora coccinea were extracted using a methanol solvent. MTT assay was carried out to determine the viability of cells after treatment with different concentrations of the extracts. Then, the Hen egg testchorioallantoic membrane (HET-CAM) assay was used as an in vivo model for chronic inflammation. This method was performed to evaluate anti-inflammatory activity by inhibiting membrane irritation on the chorioallantoic membrane, in which irritation was induced by sodium dodecyl sulfate (SDS). Then, the commercial cell line of stem cells of human exfoliated deciduous teeth cells (SHED) was cultured and total RNA was extracted, followed by reverse transcription cDNA synthesis. Multiplex PCR was performed to detect the expression levels of TNF-α, IL-1β, IL-6, IL-8, and TGF-β in both cell types. The result showed that the highest viability of cells was 78.3 % at a concentration of 1.56 mg/ml. It was found that Ixora coccinea root extracts showed good anti-inflammatory at a concentration of 1.56 mg/ml. Ixora coccinea root extracts showed good anti-inflammatory activity with 80% inhibition on the chorioallantoic membrane compared to Indomethacin, which showed 85% inhibition. Ixora coccinea root extracts showed potent anti-inflammatory effects by enhancing immune response through upregulation of inflammatory cytokines, including IL-1β, IL-6, IL-8, and TGF-β as detected by Multiplex PCR. However, the Ixora coccinea root extracts do not affect TNF-α and GMCSF. In conclusion, the present study has successfully determined the activities of Ixora coccinea extracts. The current study shows a novel finding that Ixora coccinea root extracts possess anti-inflammatory effects through immunomodulatory mechanisms.